AGRICULTURAL EXTENSION IN THE KINGDOM OF SAUDI ARABIA: DIFFICULT PRESENT AND DEMANDING FUTURE - M. Shayaa Al-Shayaa; Mirza B. Baig; Gary S. Straquadine (Journal of Animal and Plant Sciences, 2012)
Agriculture is not environmentally ideal for the Kingdom of Saudi Arabia yet agricultural sector receives great importance. The state has been making concerted efforts through its five-year development plans to develop its agriculture to ensure food security. Due to the supportive and encouraging policies of the government, and able guidance from the extension service, farmers were able to enhance agricultural production and achieve self-sufficiency, at least to some extent. A voluminous literature indicates the state now exports its products such as wheat, dates, watermelon, poultry and fresh eggs and milk. The kingdom also produces some cereals like: wheat, sorghum, barley and millet in the regions rich in water resources. Tomatoes, watermelons, eggplants, potatoes, cucumbers and onions are also grown. Encouraging response on the production of Date-palm, citrus and grapes has been experienced. Agricultural endeavours aim at moving towards achieving food security. However, in order to produce more food for the increasing population, the country realized its agricultural potential but at the cost of over-exploitation of its natural resources. The government has launched a new plan on the cultivation of crops that require less quantities of water. The government, academia and the researchers are convinced that the use of over-exploitation of water is not a sustainable practice. A balance between agricultural production and the use of its resources, particularly water, without harming the environment needs to be maintained. In the situation, the role of Agricultural Extension has become more challenging and demanding. The extension work in the state is quite difficult and presents unique problems as the farms are being managed by the overseas workers who are unable to understand extension messages being delivered in Arabic or English languages. King Saud University (KSU) has developed an Extension Centre to promote sustainable agriculture in the kingdom.
Keywords: Arid Environment; Agricultural Production; Self-sufficiency; Capacity Building; Natural Resources